Rancang Bangun Sistem Penebar Pakan Ikan berbasis Internet of Things (IoT) - Ridwan Bagus Andreyanto; Gusnul Mahesa; Muhammad Rizal; Lutfi Triyuli Evana Rizki; Firman Noor Hasan (Prosiding Seminar Nasional Teknoka, 2025)
In everyday life, both in urban and rural areas, many people enjoy keeping fish as pets because they are easy to care for and maintain. This has led to a growing interest in fishkeeping among the general public. Fish kept in aquariums require regular feeding schedules to maintain their health, making an organized and consistent feeding system essential. The ESP32 is an integrated chip developed for modern networking applications. It provides a complete and integrated Wi-Fi networking solution that can function as an application processor or serve as a Wi-Fi network controller for other processors. One of its practical applications is in the development of an automatic fish feeder based on the Internet of Things (IoT). By utilizing the ESP32 along with supporting software such as Arduino IDE, Google Firebase, and MIT App Inventor, the automatic fish feeder can operate automatically according to predefined feeding schedules. Furthermore, the system can send notifications through a website when the fish have been fed or when the feed container is empty.